Kajian Etis Teologis Terhadap Pemuda Kristen yang Melakukan Judi Online - Sondakh, Tasya Refina; Tombeng, Ineke Marlien (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2023)
This article discusses a theological ethical study of youth who engage in online gambling. This research aims to (1) find an explanation for why online gambling occurs among youth in the GMIM Bukit Sion Kanonang congregation (2) to provide understanding to young people who play online gambling in the GMIM Bukit Sion Kanonang congregation about the impacts and dangers of playing online gambling (3) to raise awareness of young people who play online gambling in the GMIM Bukit Sion Kanonang congregation so that they stop playing online gambling. This research is qualitative research with a descriptive design. The research results suggest that parents must build good communication with their children; the role of special servants, more sensitive to seeing problems in the environment, providing pastoral care for young people who play online gambling; The role of the government, providing outreach about the negative impacts of online gambling; and the public must have the courage to reprimand them if they see online gambling going on nearby.